Numerical homogenization of elastic brick masonry = Numeryczna homogenizacja sprężystych ścian ceglanych - Kuczma, Mieczysław; Wybranowska, Krystyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper is concerned with a numerical homogenization technique for determination of effective material properties of brick masonry in the elastic range. The homogenization problem is posed in the plane state of stress. The corresponding boundary value problem on a representative cell is discretized by the finite element method. The quadrilateral finite element with four nodes and eight degrees of freedom is applied and our own computer program is developed. The homogenization technique allows one to determine for masonry, which is an inhomogeneous two-phase composite medium, an equivalent homogeneous orthotropic material characterized by five material constants. The homogenized material constants can further be used in an analysis of large-scale masonry structures. The obtained results of numerical simulations are compared with predictions of the value of elastic modulus for masonry by other researches, and qualitative agreement can be observed.
Keywords: mur ceglany; homogenizacja; sprężystość; metoda elementów skończonych (MES); masonry; homogenization technique; Finite Element Method (FEM)